The Impact of BREN and BRMS Stocks' Entry into the MSCI Index on Company Value, Stock Liquidity, and the Attractiveness of the Indonesia Stock Exchange - Maulana Majied Sumatrani Saragih; Mardiana Lestary (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the impact of the inclusion of PT Barito Renewables Energy Tbk (BREN) and PT Bumi Resources Minerals Tbk (BRMS) shares in the MSCI (Morgan Stanley Capital International) index on company value, stock liquidity, and the attractiveness of the Indonesia Stock Exchange (IDX) to global investors. The research method used is a descriptive quantitative study with an event study approach and secondary data analysis in the form of market capitalization, stock prices, returns, trading volume, price-to-book value, and foreign ownership. The results show that the inclusion of BREN and BRMS in the MSCI index significantly increased company value and stock liquidity. BREN showed a more sustainable and premium increase in company value, while BRMS experienced a significant increase that was more influenced by short-term market sentiment. Furthermore, MSCI inclusion increased foreign investment flows and strengthened global market confidence in the stability and credibility of the IDX, as reflected in increased foreign ownership and market liquidity. This study confirms that the inclusion of Indonesian shares in the MSCI index not only provides benefits for companies but also strengthens the position of the domestic capital market in the global arena.